Investigation into the Decision Making Processes within Some Operating Oil & Gas Companies (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Making decisions is considered as the key role inachieving the desired goals within any organization. Moreover, making decisions in oil & gas industry is becoming a key factorfor improving the work performance throughout practicing themost effective tools and techniques. The main purpose of thispaper is to identify how individuals making their decisionswithin operating oil and gas companies.The required data for this paper were acquired byconducting several interviews with decision makers, and aquestionnaire survey was also developed, besides reviewing therelated literatures. Decision making processes in Libyan oil &gas operating companies were being investigated. The mainfindings show that over half of participants always considersafety, security and uncertainty issues when making theirdecisions, meaning that, it is a good indication of takingprecautions when making decisions. Additionally, the majorityof participants always double check their informationresources, which is also a good indication of increasing thequality decisions and enhancing the work performance. Basedon the findings, a number of recommendations were proposedfor improving the processes of making proper and effectivedecisions within this business area